The energy consumption and emission of polyurethane pavement construction based on life cycle assessment. (20th May 2020) - Cong, Lin; Guo, Guihong; Yu, Meng; Yang, Fan; Tan, Le
Abstract: Polyurethane-bounded pavement with good road performances is a new pavement form. Whether polyurethane (PU) pavement met the requirements of energy conservation, environmental protection and sustainable development or not, the energy consumption and emission of PU pavement in whole life cycle were analyzed systematically in this paper. Firstly, the life cycle of pavement was divided into six phases: material production, mixture production, transportation, construction, maintenance and recycling according to the construction technology of road in China. Based on the classification of the life cycle environmental impact assessment (LCIA), the effects of six main exhaust gases (CO2, CH4, N2 O, CO, SO2, NOx ) were divided into four categories: Global Warming Potential (GWP), Eutrophication Potential (EP), Photochemical Smog Potential (POCP) and Acidification Potential (AP). Secondly, the energy consumption and emission of each phase are studied, and the main phase with significant environmental impact was selected. Thirdly, the results of inventory would be normalized and weighted to analyze the environmental impact by the life cycle impact assessment (LCIA). The LCIA method was environmental design of industrial product 97 (EDIP 97). Results show that the construction of PU pavement is conducive to energy conservation. Besides, the energy consumption of mixture production phase is the largest in asphalt pavement, and it is material production phase in PU pavement. In terms of emission, the emissions mainly occur in material production and mixture production phases in asphalt pavement, and it is material production phase in PU pavement. Under the same structure, the construction of PU pavement is not conducive to reducing the emission, and will enlarge the GWP, EP and AP. For example, the CO2, N2 O and NOx emissions of PU pavement are 1.98, 5.30 and 2.35 times higher than that of asphalt pavement respectively, but the CO emission of asphalt pavement is 3.86 times higher than that of PU pavement. Furthermore, the results of LCIA show that the score of all environmental impact of PU pavement is little smaller than that of asphalt pavement after normalization and weighting. However, the road performances of PU pavement are much better than that of asphalt pavement. With the same environmental impact, PU pavement has a longer service life. It is summarized that PU pavement meets the requirements of environmental protection and sustainable development in the long run. This is conducive to the promotion and application of PU pavement. Highlights: The energy consumption and emission of PU pavement in life cycle were studied. The goal and scope definition of this study were determined. The key phases of high energy consumption and emission were identified. The comprehensive environmental impact assessments of asphalt pavement and PU pavement are conducted.